1997
DOI: 10.1007/s001250050674
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of inhibitors of aldose reductase and sorbitol dehydrogenase on neurovascular function, nerve conduction and tissue polyol pathway metabolites in streptozotocin-diabetic rats

Abstract: Elevated polyol pathway activity has been implicated in the development of diabetic complications, including neuropathy [1]. In diabetic models, inhibitors of the first enzyme in the pathway, aldose reductase, prevent or correct nerve conduction velocity (NCV) and regeneration deficits [2][3][4][5][6][7][8][9][10][11][12][13]. Clinical trials of aldose reductase inhibitors (ARIs) have shown modest improvements in neurological symptoms, NCV, sensory measures, and an increase in nerve fibre regeneration [14-17] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
106
5
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 72 publications
11
106
5
1
Order By: Relevance
“…Immediately after determination of MNCV, sciatic nerve endoneurial nutritive blood flow was determined as described by Cameron et al [33,50]. The trachea was intubated for mechanical ventilation and a carotid cannula inserted to monitor mean arterial blood pressure.…”
Section: Endoneurial Blood Flowmentioning
confidence: 99%
“…Immediately after determination of MNCV, sciatic nerve endoneurial nutritive blood flow was determined as described by Cameron et al [33,50]. The trachea was intubated for mechanical ventilation and a carotid cannula inserted to monitor mean arterial blood pressure.…”
Section: Endoneurial Blood Flowmentioning
confidence: 99%
“…Some groups [29±31] have reported that SDIs reduce nerve conduction deficit induced by diabetes. Others failed to find improved nerve conduction in diabetic rats treated with SDI compared with an untreated diabetic group [4] or in SDH-deficient diabetic mice compared with diabetic mice with normal SDH levels [32].…”
mentioning
confidence: 99%
“…[Diabetologia (1999) 42: 1187±1194] pletely understood. A number of reports [1,2,4, 10±14] link vascular [4, 15±20], metabolic [21±24] and neurotrophic [25±27] imbalances that are induced by diabetes to the activity of the first half of the sorbitol pathway, aldose reductase. Some investigators [28,29] have hypothesized that adverse consequences of increased sorbitol pathway activity in the diabetic nerve are not due to aldose reductase activation itself, but are related to the second half of the sorbitol pathway, sorbitol dehydrogenase (SDH).…”
mentioning
confidence: 99%
See 2 more Smart Citations